IMPROVING THE LISTENING ABILITY OF ELEMENTARY SCHOOL STUDENTS THROUGH THE USE OF AUGMENTED REALITY-BASED LEARNING MEDIA - Dudu Suhandi Saputra; Sigit Vebrianto Susilo; Tita Mulyati (Universitas Pendidikan Indonesia, 2023)
This research is motivated by the low listening ability of elementary school students. The purpose of this study is to determine the improvement of listening skills of fifth-grade elementary school students by using augmented reality-based learning media. This study uses an experimental model with a pretest-posttest control group design with a sample of 60 students. The instrument used in this study is to use a listening ability test, besides that the test results are analyzed by looking at the differences in students' listening abilities between students who learn by using augmented reality-based learning media and students who learn by using conventional learning media. The results showed that (1) there was a very significant difference in listening ability between the experimental class and the control class, and (2) the listening ability of students who studied using augmented reality-based learning media was higher than students who studied using conventional learning media. Through the use of augmented reality media, learning activities can be more fun and meaningful so that students do not feel bored studying learning materials.